Acute Lung Injury (ALI): Evaluating and Improving Functional Outcomes in Survivors - Mackney, Jennifer Helen (Curtin University, 2019)
This research examined successive phases of recovery in people who had survived an intensive care unit (ICU) admission for acute lung injury (ALI). On ICU discharge, when compared with a general ICU population, ALI survivors experienced greater impairment in exercise capacity and strength, and when examined after hospital discharge, these limitations were related to deconditioning, and impaired pulmonary and cardiac function. A subsequent high intensity training program was safe and effective in improving exercise capacity.